2022
DOI: 10.35848/1347-4065/ac7761
|View full text |Cite
|
Sign up to set email alerts
|

New-parallel connection of the Helmholtz resonator with embedded apertures for low-frequency broadband sound absorption

Abstract: We designed/proposed kinds of new-parallel connection of the Helmholtz resonator with embedded apertures. The design rule of the resonator, aperture and length of the embedded hole has much influence on the sound absorption characteristics of the metamaterials. The multiple nearly perfect sound absorption peaks in a wide frequency band were obtained. The results show that by accurately balancing the coupling parameters of the new-parallel connection of the Helmholtz resonator with embedded apertures, the reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…According to the analysis of influence of structural parameters to sound absorption performance of double resonators and the similar research in literatures [ 41 , 42 , 43 , 44 ], it could be concluded that length of the cavity was the most suitable parameter to be the adjustable variable, which was easy to realize the adjustment for an already prepared acoustic metamaterial and it did not influence relative independence of each chamber. Thus, this analysis provided theoretical foundation and basis for the proposed APH-AM in this research.…”
Section: Materials and Designmentioning
confidence: 74%
See 2 more Smart Citations
“…According to the analysis of influence of structural parameters to sound absorption performance of double resonators and the similar research in literatures [ 41 , 42 , 43 , 44 ], it could be concluded that length of the cavity was the most suitable parameter to be the adjustable variable, which was easy to realize the adjustment for an already prepared acoustic metamaterial and it did not influence relative independence of each chamber. Thus, this analysis provided theoretical foundation and basis for the proposed APH-AM in this research.…”
Section: Materials and Designmentioning
confidence: 74%
“…Furthermore, the resonance frequencies f 0 of resonator 2 moved to the low frequency direction along with the increase of length of its cavity, which was easy to realize adjustment by moving the back panel in the chamber relative to length or diameter of the aperture and other parameters. Therefore, length of the cavity was selected as the adjustable variable for the proposed APH-AM in this research, which was same with the selection in some literatures [ 41 , 42 , 43 , 44 ]. The absorption peak was controlled through adjusting the geometric parameters of the Helmholtz resonator with embedded apertures by Zhang et al [ 41 ], and the absorption bandwidth could also be flexibly adjusted with a fixed thickness.…”
Section: Materials and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited by the preparation technique and fabrication accuracy, the shape of the embedded aperture is cylindrical and the cross-sectional shape is circular, although the shape of the chamber can be adjusted for ease of installation [ 16 , 17 , 18 , 19 , 20 ]. Zhang et al [ 16 ] designed kinds of new parallel connections of the HR with the embedded aperture, the working wavelength of which was about 57 times its total thickness of 43 mm. The average sound absorption coefficient was as high as 0.8.…”
Section: Introductionmentioning
confidence: 99%
“…A preferable option is to incorporate multiple components in parallel, forming a continuous broad absorption band by assembling diverse absorption peaks. Several broadband absorbers have been reported by coupling multiple HRs [22,[39][40][41][42] or space-coiling structures [43][44][45][46]. These options have a common element of exploiting a multi-modal system, each mode having low dissipation, to achieve broadband absorption [47].…”
Section: Introductionmentioning
confidence: 99%